Biomanufacturing of CdS quantum dots1. Issue 7 (6th July 2015) - Yang, Zhou; Lu, Li; Berard, Victoria F.; He, Qian; Kiely, Christopher J.; Berger, Bryan W.; McIntosh, Steven
<x xml:space="preserve">Abstract</x> A strain of Stenotrophomonas maltophilia is engineered to achieve size controlled synthesis of water soluble CdS quantum dots.